The Role of Perceived Value in Mediating the Effect of Store Atmosphere and Service Quality on Repurchase Intention at OB.Second Outlets - Robby Wahyu Al Ayubi; Aang Curatman; Jefry Romdonny (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this study is to examine how customers of OB.Second stores in Cirebon use perceived value to mediate the impact of store atmosphere and service quality on repurchase intention. The fierce rivalry in the thrifting sector and the significance of keeping clients through a satisfying shopping experience serve as the foundation for the research background. This study uses a quantitative methodology, collecting data from 300 respondents who have previously made purchases at OB.Second via a Google Form. SEM-PLS was used to analyze the data using SmartPLS software.The findings show that perceived value is positively and significantly impacted by store atmosphere and service quality. Furthermore, it has been demonstrated that repurchase intention is positively and significantly impacted by perceived value. Other findings show that the store atmosphere and service quality directly affect repurchase intention, but their impact intensifies when mediated by perceived value.The study concludes that enhancing the store's atmosphere and the quality of service can foster a positive perceived value among customers, thereby motivating them to make repeat purchases.